Production of Chitooligosaccharides with Antibacterial Potential via Crude Chitinase Enzymes from Marine Fungi - Apiradee Pilantanapak (Science Faculty of Chiang Mai University, 2019)
Twenty marine fungi from driftwoods and Nypa fruticans in the marine environments were screened for chitinase production in culture filtrates. Two best strains with the highest chitinase activity were selected to produce crude chitinase enzyme. Thereafter chitooligosaccharide mixtures were produced by hydrolyzing native chitosan with crude chitinase fungal enzyme and these were then assess for their antibacterial activity against 2 Gram positive and 2 Gram negative bacteria. Two marine fungi Astrosphaeriella sp. BUSK 55-1 and Oxydothis sp. BUSK 43-2, were selected for this study. The chitinase activities at day 21 were 16.9 mU/mL and 22 mU/mL, respectively. Hydrolysis of native chitosan (720 kDa, 86.5 % degree of deacetylation) by approximate 0.8U crude chitinase of these two marine fungi yielded chitooligosaccharides mixtures with an average molecular weight of 8.54 kDa-8.62 kDa. Using the standard disc paper method, the chitooligsaccharides displayed antibacterial activity against all tested bacteria; Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis. The best activity was oligosaccharides prepared from chitinase enzyme of Astrosphaeriella sp. BUSK 55-1. The standard disc contained at least 250 ppm and at least 500 ppm oligosaccharides obtained from this enzyme displayed inhibition against B. subtilis and S. aureus, respectively.